Analysis of Indonesian government foreign debt - Dyah Tri Larasati; Timbang Sirait (Privietlab, 2026)
In the government sector, there is still little research on foreign debt issues. Monthly time series data and a combination of macroeconomic variables as independent variables are unique approaches that have not been used in previous studies. This study aims to analyze the short- and long-term impacts of foreign exchange reserves, net exports, exchange rates, inflation, and London Interbank Offered Rate (LIBOR) on the Indonesian government foreign debt from January 2014 to December 2022. This study uses cointegration and the Error Correction Mechanism (ECM). Based on 108 monthly observations spanning a nine-year timeframe, the results reveal that Indonesian government foreign debt is positively and significantly influenced by foreign exchange reserves in the long run. Conversely, inflation and the exchange rate exert a negative and significant impact. Within the short-term analysis, foreign exchange reserves continue to exhibit a positive and significant correlation, whereas negative and significant effects are observed for the LIBOR interest rate, inflation, and the exchange rate. Finally, the study finds that net exports consistently show no significant influence in the short or long term. The empirical implication of this study is to determine the policies and programs that are influential in maintaining the stability of Indonesian government foreign debt in both the short and long term.